Description of new genus and species of Ochlerini from Central America (Hemiptera: Pentatomidae: Discocephalinae) - Matesco, Viviana Cauduro; Grazia, Jocélia; Campos, Luiz Alexandre (Zootaxa, 2007)
Parastalius gen. nov. is described for Stalius trisinuatus Rolston; the external genitalia of the latter are redescribed; and a new species is described from Costa Rica, Parastalius rolstoni sp. nov.